Pengaruh Promosi dan Harga Terhadap Minat Beli Konsumen Pada Produk Macinos - Ramadhona, Okta; Wicaksono, Haryo; Sugeng, Novita Widyastuti (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2117, 2026)
This study aims to analyze the effect of promotion and price on consumer purchase intention toward Macinos products. The study employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to consumers who had purchased or tried Macinos products. The sampling technique used was purposive sampling based on predetermined criteria. The research instrument employed a Likert scale, and the data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that promotion has a positive and significant effect on consumer purchase intention. This finding suggests that more attractive, informative, and relevant promotional activities conducted by Macinos can increase consumers’ intention to purchase its products. Meanwhile, price does not have a significant effect on consumer purchase intention. This finding indicates that price perception is not the primary factor determining consumers’ purchase intention toward Macinos products. Furthermore, promotion and price simultaneously have a significant effect on consumer purchase intention. Therefore, Macinos is advised to prioritize the development of creative and informative promotional strategies through social media while maintaining competitive prices that are consistent with the value of the products offered. Keywords: promotion, price, purchase intention, consumer